Pengaruh Jenis Kemasan dan Lama Penyimpanan terhadap Serangan Serangga dan Sifat Fisik Ransum Broiler Starter Berbentuk Crumble - Yuli Retnani; Dimar Wigati; Abdul Djamil Hasjmy (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
Storage  of  feedstuff  is  required  because  development  of  farm  must  be  made  balance  with availability of adequate feedstuff. Storage will influence physical properties of feedstuff. Packaging is the one of methods to take care product. Damage by environment can be controlled by packaging.  This study  was  arranged  in  a  Completely  Randomize  Design  with  factorial  design  (4x5)  with  four replications. The first factor was packaging type (guny sack, plastic sack, paper packaging, and plastic packaging). The second factor was storage (0, 2, 4, 6, 8 weeks). The parameters observed were: water content, water activity, particle size, specific density, bulk density, compacted bulk density, angle of repose  and  insect  attack.  Data  were  analyzed  using analysis  of  variance  (ANOVA)  and  differences between treatments were determined with Duncan test. The results showed that packaging type highly significantly affected (p<0.01) the moisture content, water activity, and compacted bulk density. Storage highly significantly affected (p<0.01) the moisture content, water activity, particle size, specific density, bulk density, compacted bulk density, and angle of repose. Insect attack was increase  on guny sack, especially at four weeks of storage. Paper packaging and plastic packaging can take care feedstuff from insect attack until eight weeks, but plastic sack until four weeks, and guny sack until two weeks. Guny sack, plastic sack, paper packaging, and plastic packaging can take care physical properties of feedstuff until eight weeks.